Introducing Complementary Foods to Infants: Does Age Really Matter? A Look at Feeding Practices in Two European Communities: British and Italian. Issue 3 (3rd July 2019) - Costantini, Cristina; Harris, Gillian; Reddy, Vasudevi; Akehurst, Lucy; Fasulo, Alessandra
ABSTRACT: Advice about the age for introducing complementary food to infants varies across European countries. Little is known about the actual practice of complementary feeding (CF) in the face of different advice from health professionals within Europe, nor about the impact of different ages of onset of CF on infant food acceptance. This longitudinal study aimed to explore CF in two European communities, British and Italian and to investigate whether infant age of CF influenced infant food acceptance. Forty-six mothers were interviewed before the onset of CF (Visit 1), one week after CF (Visit 2), and at 7 months of infant age (Visit 3), and infant mealtimes were video-recorded at Visits 2 and 3. CF occurred in both groups at a similar range of ages. CF age did not affect infant food acceptance at either Visit. Advice on CF should be based on cultural and individual differences.